Cyanobacteria as Nanogold Factories II: Chemical Reactivity and anti-Myocardial Infraction Properties of Customized Gold Nanoparticles Biosynthesized by Cyanothece sp. - Nancy S. Younis; Esam M. Bakir; Maged E. Mohamed; Nermin A. El Semary (Marine Drugs, 2019)
Cyanothece sp., a coccoid, unicellular, nitrogen-fixing and hydrogen-producing cyanobacterium, has been used in this study to biosynthesize customized gold nanoparticles under certain chemical conditions. The produced gold nanoparticles had a characteristic absorption band at 525−535 nm. Two types of gold nanoparticle, the purple and blue, were formed according to the chemical environment in which the cyanobacterium was grown. Dynamic light scattering was implemented to estimate the size of the purple and blue nanoparticles, which ranged from 80 ± 30 nm and 129 ± 40 nm in diameter, respectively. The highest scattering of laser light was recorded for the blue gold nanoparticles, which was possibly due to their larger size and higher concentration. The appearance of anodic and cathodic peaks in cyclic voltammetric scans of the blue gold nanoparticles reflected the oxidation into gold oxide, followed by the subsequent reduction into the nano metal state. The two produced forms of gold nanoparticles were used to treat isoproterenol-induced myocardial infarction in experimental rats. Both forms of nanoparticles ameliorated myocardial infarction injury, with a slight difference in their curative activity with the purple being more effective. Mechanisms that might explain the curative effect of these nanoparticles on the myocardial infarction were proposed. The morphological, physiological, and biochemical attributes of the Cyanothece sp. cyanobacterium were fundamental for the successful production of “tailored” nanoparticles, and complemented the chemical conditions for the differential biosynthesis process. The present research represents a novel approach to manipulate cyanobacterial cells towards the production of different-sized gold nanoparticles whose curative impacts vary accordingly. This is the first report on that type of manipulated gold nanoparticles biosynthesis which will hopefully open doors for further investigations and biotechnological applications.